Fundus autofluorescence and optical coherence tomography findings in thiamine responsive megaloblastic anemia - Ach, Thomas; Kardorff, Rüdiger; Rohrschneider, Klaus (Retinal cases & brief reports, 2015)
To report ophthalmologic fundus autofluorescence and spectral domain optical coherence tomography findings in a patient with thiamine responsive megaloblastic anemia (TRMA).
Gesehen am 16.10.2020